PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS V DI MI HIDAYATUL MUBTADI’IN KERTOSARI PURWOSARI PASURUAN - Asro Masaal; M. Jamhuri (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
The Problem Based Learning model or often known as problem based learning is a teaching model characterized by the existence of real problems as a context for students learning critical thinking and problem solving skills and gaining knowledge. This study aims to determine the application of the Problem Based Learning model in Fiqh learning in Class V MI Hidayatul Mubtadi'in Kertosari Purwosari. And to find out the results of the application of the Problem Based Learning model in the subject of Fiqh in Class V MI Hidayatul Mubtadi’in Kertosari Purwosari. This study uses a qualitative approach in this study, data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the application of the Problem Based Learning model in the subject of Fiqh in MI Hidayatul Mubtada’in Kertosari Purwosari is made in several groups, adjusted for the number of students present when participating in learning activities, and so forth. However, students and teachers remain enthusiastic in learning in the classroom And for the results for this Problem Based Learning process of learning activities students do not feel bored, the way students learn to find answers is also active, because before the activity is carried out students learn good enough or satisfying the material, so there are levels in the teaching and learning process of subjects This jurisprudence. According to the teacher of jurisprudence the learning process of students becomes better compared to the others.